Treatment of strokes in the emergency department of N’Djamena general hospital: study of delays, care and clinical course of patients in the first hours. - Madjiténgar RATAÏNGAR; Baba DIALLO; Fidèle BINAM; Alexandre NKOUM; Samson NKOUMOU; Aboubacar S.T. KANE; Oumar SANGHO; Aissata Koné dite Néné Tjini (Jour Med Resh and Health Sci, 2021)
Introduction: Meeting the deadlines for treatment of Cerebral Vascular Accidents (CVA) could allow victims to maintain an optimal functional level in interaction with the environment. To study the management, the delays, the care and the clinical evolution of the patient’s victims of the cerebrovascular accidents during the first hours in the emergency department of the General Hospital of Reference of N’Djamena (HGRN). Material and methods: This was a descriptive, analytical cross-sectional study. Included in the study were all stroke victims hospitalized in the HGRN emergency room. The sample size was 60 patients. The questionnaire and the observation grid were the collection tools. The data were entered by Cspro software and analyzed on Excel and SPSS. Results: The mean age of the patients was 54.65 ± 11.6 years. About 2/3 of the study population 67% were female with a sex ratio of 2 in favor of women. All patients were transported to the emergency room by non-medical means. Ischemic strokes represented 66.67% of cases. The overall death rate was 13.33%. About 36.3% of patients arrived at the emergency room between 4:30 a.m. and 6 a.m. after the onset of the first symptoms. The clinical outcome of the patients was unfavorable in 55% of cases, including 47.5% of ischemic strokes. Conclusion:We do not have a link between age and clinical course. All patients were transported to the emergency room by non-medical means. Raising public awareness of the signs and symptoms of stroke could help reduce complications of the disease.